Computing in Astronomy: To See the Unseen. - Pankratius, Victor; Mattmann, Chris (Computer (00189162), 2014)
Advances in computing have empowered astronomers to explore the universe in greater detail. Software-defined instruments relying on digital data capture and processing are more powerful than ever and continue to bring us new knowledge about the universe and our place in it.